The cost benefit analysis and potential emission reduction evaluation of applying wall insulation for buildings in Malaysia - Shekarchian, M.; Moghavvemi, Mahmoud; Rismanchi, B.; Mahlia, T.M.I.; Olofsson, T. (Elsevier, 2012)
Due to the rapidly increasing number of air-conditioned spaces in buildings, the electricity demand has significantly increased during the past decade in Malaysia. The present energy analysis attempts to predict the long term environmental impact of utilizing thermal insulation materials for exterior walls of Malaysian buildings. The optimum insulation thickness is mainly influenced by local electricity tariff rate, and the capital insulation outlays. In the present work, some of the commonly used insulators available in the Malaysian market were analyzed. The results show that 2.2 cm of fibreglass-urethane produces the largest cost savings, of around 1.863US$/m 2 and is the most economically feasible insulation material that reduces the annual CO 2 emission production level by 16.4 kg/m 2. The main focus of the survey is to predict the potential emission production fluctuation for over the next 20 years. In this regard, three different scenarios were introduced, based on different electricity production policies. It was revealed that the increase in the contribution of renewable power plants on one hand, and phasing out of the conventional thermal coal plants on the other will substantially lead to a diminished CO 2 emission in long term.